Analisis Sistem Transportasi Logistik (Studi Kasus: Pergudangan Kota Parepare) - Saputra, Udes; Hakzah; Misbahuddin (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Parepare is a commercial city that distributes various types of commodities and industrial products every day to lots of whether inside or outside South Sulawesi. Therefore, the role of warehousing is very important to support the distribution process. This research aims to determine the characteristics and choice of transportation modes for goods and warehouse commodities using the Analytical Hierarchy Process method based on surveys and interviews with 200 respondents. The results of the research show that the characteristics of the transportation modes that used are pick up, 2 axle trucks, 3 axle trucks and trailer trucks, dominated by commodity yields of 56.50%, load prices of 85 - 120 million by trailer trucks and loads above 30 tons with more than 15 hours of travel time. The choice of the most efficient mode of transportation for distributing goods and warehousing commodities is a 2 axle truck with a priority weight percentage of 0.30%.